Temperature analysis of solar prominences by multi-wavelength observations. (18th March 2020) - Okada, Sanetaka; Ichimoto, Kiyoshi; Machida, Aki; Tokuda, Satomi; Huang, Yuwei; UeNo, Satoru
Abstract: The aim of this paper is to determine the kinetic temperature of solar prominences from widths of emission lines with a careful evaluation of its validity, and to investigate the spatial distribution of the non-thermal velocity and the kinetic temperature in prominences. Spectroscopic observations of prominences were carried out using the Domeless Solar Telescope at the Hida observatory in four emission lines, i.e., Hα 656.3\: nm, Hβ 486.1\: nm, Ca^+ IR 854.2\: nm, and Ca^+ K 393.4\: nm. We found systematic differences in temperature and its spatial distributions in prominences obtained from different pairs of spectral lines. The reason for the difference is that the intrinsic widths of emission lines determined by a single-slab model are different for optically thick and thin lines, and can be attributed to the assumption of a Gaussian profile of the non-thermal broadening in the single-slab model. With numerical experiments, we found that the observed differences among line pairs can be reproduced by a multi-slab model, in which each slab has different non-thermal broadening and line-of-sight velocity. The most accurate evaluation of the temperature is obtained with the pair of Hβ and Ca^+ IR in our selection. Based on these results, we found the typical kinetic temperature of prominences to be 8000–12000\: K, which is significantly higher than the temperature determined by radiative balance and suggests the presence of mechanical heating in prominences. Also suggested is the presence of positive spatial correlation between non-thermal velocity and temperature. We revisit past observational results on the prominence temperature and discuss the reason for discrepancies among them.